Monetary policy rules for Russia - Akram Esanov; Christian Merkl; Lúcio Vinhas de Souza (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
The paper reviews the recent conduct of monetary policy and the central bank's rule-based behavior in Russia. Using different policy rules, we test whether the central bank in Russia reacts to changes in inflation, output gap and the exchange rate in a consistent and predictable manner. Our results indicate that during the period of 1993-2002 the Bank of Russia has used monetary aggregates as a main policy instrument in conducting monetary policy.
URN:NBN:fi:bof-201408072127
Keywords: 330; monetary policy rules; exchange rate; central bank; Russia; Geldpolitik; Regelgebundene Politik; Inflationsbekämpfung; Wechselkurspolitik; Russland